L-arginine pretreatment ameliorates Lipopolysaccharide-induced thyroid gland dysfunction in male albino rats - basma osama mohamed (South Valley University, 2021)
Bacterial infection is one of the most common causes of systemic inflammatory syndrome known as sepsis. Previous studies have been shown that sever sepsis was often complicated with secondary multiple organs dysfunction. This syndrome may greatly affect thyroid gland function leading to thyroid gland dysfunction. The objective of this study was to elucidate the effect of bacterial endotoxin (lipopolysaccharide, LPS) on thyroid gland function. The study extended to investigate the role of L-arginine (L-Arg) as immunomodulator in LPS-induced systemic inflammation. Eighty adults, male Wistar rats were randomly divided into four equal groups: The control group was intraperitoneally (IP) injected with physiological sterile saline (0.9% NaCl at dose 1 ml/kg body weight (BW)); LPS-treated group was injected with a single dose of LPS (1 mg/kg BW, IP); L-Argtreated group was injected with L-Arg (10 mg/kg BW, IP) once per day for 7 consecutive days; and L-Arg + LPS treated group was injected with L-Arg (10 mg/kg BW, IP) once per day for 7 consecutive days followed by a single dose of LPS (1 mg/kg BW, IP). Histopathological changes of thyroid gland, serum triiodothyronine (T3), thyroxine(T4), and thyroid stimulating hormone (TSH) levels were examined at 6, 12, 24 and 72 hours (h) after the last injection. Treatment of rats with a single dose of LPS alone resulted in thyroiditis which manifested by decreased serum T3 and T4 levels and severe necrosis of the thyroid follicles. However, in L-Arg-treated endotoxemic rats, pretreatment with L-Arg attenuated the LPS-induced acute thyroid gland injury.